Equality Governance via Policy Analysis? : The Implementation of Gender Impact Assessment in the European Union and Gender-based Analysis in Canada - Sauer, Arn Thorben (2018)
Gender impact assessment has been both celebrated as a beacon of hope for the cause of gender equality and criticised as being ineffectual. More than 20 years of gender mainstreaming have demonstrated that equality governance with and through impact assessment is an intersectional and still evolving process.Arn T. Sauer's study examines the instruments of gendered policy analysis and the conditions under which they are being used by the Canadian federal government and the European Commission. Interviews with experts from public administration and instrument designers as well as document analyses reveal benefits and challenges and show that the success of equality governance depends upon whether knowledge about gendered policy and appropriate administrative practices are embedded, embodied and entrenched in public administration